2011
DOI: 10.3171/2011.2.jns10998
|View full text |Cite
|
Sign up to set email alerts
|

An extent of resection threshold for newly diagnosed glioblastomas

Abstract: Object. The value of extent of resection (EOR) in improving survival in patients with glioblastoma multiforme (GBM) remains controversial. Specifically, it is unclear what proportion of contrast-enhancing tumor must be resected for a survival advantage and how much survival improves beyond this threshold. The authors attempt to define these values for the patient with newly diagnosed GBM in the modern neurosurgical era.Methods. The authors identified 500 consecutive newly diagnosed patients with supratentorial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
922
12
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 1,352 publications
(970 citation statements)
references
References 13 publications
29
922
12
7
Order By: Relevance
“…In patients with newly diagnosed glioblastomas, increased EOR parallels improvements in overall survival, even at the highest levels of resection, and subtotal resections as low as 78% confer survival benefits. 9) Our results are similar to these findings (Table 1). In our series, the resection rate of LGG was lower than that of HGG.…”
Section: Discussionsupporting
confidence: 83%
“…In patients with newly diagnosed glioblastomas, increased EOR parallels improvements in overall survival, even at the highest levels of resection, and subtotal resections as low as 78% confer survival benefits. 9) Our results are similar to these findings (Table 1). In our series, the resection rate of LGG was lower than that of HGG.…”
Section: Discussionsupporting
confidence: 83%
“…[3][4][5][6][7] As the extent of surgical resection is known to significantly impact patient prognosis [8][9][10] , whether "biopsy-only" GBM patients receive a significant survival benefit to CRT over radiotherapy (RT) alone is less clear.…”
Section: Introductionmentioning
confidence: 99%
“…16) The results indicated that resection exceeding 78% can impact patient survival, and that this trend continues even at the highest levels of resection. The study included elderly (range 20-90 years, median 60 years) and low KPS (range 20-100%, median 80%) patients.…”
Section: Discussionmentioning
confidence: 94%
“…17) The median OS was 12.2 months among 500 GBM patients (median age 60 years, median preoperative KPS 80%) in another institute. 16) The following variables were found to be significant prognostic factors favoring longer survival by multivariate analysis in the subtotal and partial groups: younger age, TMZ therapy, 60 Gy irradiation, MGMT-negative, and more than subtotal resection (Table 2). Some were previously reported to be prognostic factors for GBM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation